Device Discovery Schemes for Energy-efficient Cluster Head Rotation in D2D - Bhaskara Narottama; Arfianto Fahmi; Budi Syihabuddin; Desti Madya Saputri; Patricius Evander Christy; Obed Rhesa Ludwiniananda (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this paper, novel device discovery approaches for the Cluster Head Rotation, which is a state-of-the-art method for the Device-to-Device communication, are proposed. The device discovery is the process to detect and to include new devices in the Device-to-Device communication. The proposed device discovery is aimed to attain energy efficiency for the communication devices. We propose two schemes for the device discovery: eNB-assisted and independent device discovery. Compared to previous work, the proposed device discovery is utilizing the cluster head rotation method, to achieve better energy efficiency. In this work, several simulations were performed and discussed for both schemes. In the first simulation, the device energy consumption is examined. After that, the number of devices that get rejected is studied. The device discovery processes in multi cluster head scenario, which is Cluster Head Rotation, are examined in this paper. The result of the simulation shows that eNB-assisted device discovery can provide better energy efficiency. Also, the number of rejected devices of the eNB-assisted device discovery is slightly lower than independent device discovery.